Impact of Prophylactic Continuous Positive Airway Pressure on Transient Tachypnea of the Newborn and Neonatal Intensive Care Admission in Newborns Delivered by Elective Cesarean Section - Celebi, Miray Yilmaz; Alan, Serdar; Kahvecioglu, Dilek; Cakir, Ufuk; Yildiz, Duran; Erdeve, Omer; Arsan, Saadet; Atasay, Begum (American Journal of Perinatology, 2016)
Objective This study aims to evaluate the effect of the prophylactic continuous positive airway pressure (CPAP) administration in the delivery room to newborns who were delivered by elective cesarean section (CS).Study Design Inborn infants with gestational age between 340/7 to 386/7 and born by elective CS were prospectively randomized to receive either prophylactic CPAP for 20 minutes via face mask or standardized care without CPAP in the delivery room. Primary outcomes were the incidence of transient tachypnea of the newborn (TTN) and neonatal intensive care unit (NICU) admission due to respiratory distress.Results A total of 259 infants with a mean gestational age of 37.7 ± 0.8 weeks and birth weight of 3,244 ± 477 g were included. A total of 134 infants received prophylactic CPAP and 125 received control standard care. The rate of NICU admission was significantly lower in prophylactic CPAP group (p = 0.045). Although the rate of TTN was lower in the prophylactic CPAP group, the difference was not statistically significant (p = 0.059). The rate of NICU admission due to respiratory distress was significantly higher in late-preterm cohort than early-term cohort (p < 0.0001).Conclusion Prophylactic CPAP administration decreases the rate of NICU admission without any side effect in late-preterm and early-term infants delivered by elective CS.
Keywords: continuous positive airway pressure; late preterm; early term; delivery room; transient tachypnea of the newborn